THE EFFECT OF GUIDED WRITING STRATEGY ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Fandy Raymond Napitupulu; Tjut Ernidawati (Universitas Negeri Medan, 2015)
This study is an attempt to discover the effect of applying Guided Writing Strategy on students’ achievement in writing descriptive text. It was conducted by using experimental research design. The Population of this research was the eighth (VIII) grade students of SMP Tri Sakti Lubuk Pakam which has three parallel classes. The samples of this research were taken by through lottery. They were class VIII 3 became the experimental group and class VIII 2 became the control group. The experimental group was taught by using Guided Writing Strategy while the control group without treatment. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. The result shows that the value of t-observed is higher than the value of t-table. (5.56 > 1.67 (α = 0.05)) with the degree of freedom (df) = 70. It means that there is a significant effect of applying Guided Writing Strategy on students’ achievement in writing descriptive text. So, the alternative hypothesis (Ha) is accepted.